An Analysis of public health expenditure and infrastructure in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Health standards in India have been steadily improving, indicating a robust health infrastructure. Providing better healthcare facilities has been a major challenge since independence. Growing population and economic backwardness have posed challenges for the government in ensuring access to healthcare for the general public. The state of healthcare facilities, especially in rural areas, remains poor, resulting in the gap between rural and urban health indicators. Along with providing healthcare facilities, the government has also implemented population control and family planning programs alongside health services, thus establishing a multifaceted and multi-purpose healthcare infrastructure in India. After 1991, in the changing economic conditions, health services were not spared by privatization and liberalization policies. Positive changes in per capita income and reduced government responsibilities following privatization and liberalization have opened the way for increased spending on improved healthcare. The government has increased public health spending and is making efforts to provide modern healthcare services free of charge, helping to ensure widespread access to improved healthcare to a wider population.This research paper presents a comprehensive assessment of India's public health infrastructure, highlighting public expenditure on the country's vast healthcare system, as well as the availability and trends of public health infrastructure.